Thermal structure of Venus׳ nightside mesosphere as observed by infrared heterodyne spectroscopy at 10 μm. (August 2015) - Stangier, Tobias; Hewagama, Tilak; Sornig, Manuela; Sonnabend, Guido; Kostiuk, Theodor; Herrmann, Maren; Livengood, Timothy
Abstract: Ground-based heterodyne spectroscopy is used to observe the night side of Venus by probing single pressure broadened CO2 absorption lines. From the pressure induced line broadening, the predominant temperature at different altitude layers can be deduced. It is found, that heterodyne spectroscopy is sensitive to probe the mesosphere between 60 km and 90 km with an altitude resolution of 4.5 km . During two observing campaigns in March and May 2012, four different locations on the planet were investigated. Herein, we report on the retrieval of vertical temperature profiles in the nightside atmosphere of Venus. Retrieval of atmospheric parameters is based on a Levenberg–Marquard χ 2 optimization that iteratively compares observed data to telluric transmittance corrected Venus׳ top-of-atmosphere spectra calculated using a radiative transfer algorithm. The deduced profiles are compared to the Venus International Reference Atmosphere and some found to be in satisfactory agreement. Sub-Doppler resolution Infrared heterodyne observations can provide temperature measurements that complement existing sub-mm and space based observations. Abstract : Highlights: Retrieval of atmospheric temperature profiles from ground-based IR heterodyne observations. Observations of pressure broadened CO2 absorbtion features on Venus nightside. Validation of newly developed retrieval algorithm. Investigation of thermal properties of Venus' nightside mesophere.